Public health reimagined - Julian Abel; Allan Kellehear (Wiley, 2023)
Abstract This essay offers a critical assessment and reflection on the field of public health based on policy directions and themes gleaned from the historical story of John Snow and the Broad Street pump in 19th century London and recent international responses to Covid‐19. Dominant public health strategies, especially for infectious disease emergencies, demonstrate a persistent tendency towards authoritarian claims about science that marginalise concerns about human rights, showing disregard for interprofessional and partnership working, antipathy toward critical voices and a retreat into old ideas about death and dying as medical failure. There is also neglect of the fundamental importance of social relationships as a primary source of health and well‐being. Recommendations for a more positive approach for the future of public health are made. These include restoration of, and recommitment to, partnership working with communities, experiential literacy, the prioritising of social support and incentives over negative sanctions, and the acknowledgement and support of end‐of‐life experiences as a focus for special and overdue public health attention. These suggestions advocate for the application of 'new' public health priorities to address and rebalance the limitations of the old, usual approach.